The Contentious Debate over the Language Literature Division - Mart Cagri Tugrul (Journal of Language and Cultural Education, 2018)
In the early 20th century literature was woven into language curriculum to endorse learners to acquire language structures and perform drills successfully. The actual use of the target language upstaged grammar instruction as the primary focus of language learning in the fields of language pedagogy. In the late 1960s and 1970s literature fell into disuse on the grounds that it was not in conformity with standard grammar rules and the widespread perception was that literature was complex and inaccessible for learners. In the late 1970s and 1980s a decisive swing against literature was experienced and literature came into prominence to enable learners to make huge leaps in language learning. Learners can reap many benefits from the inclusion of literature in foreign language teaching. In attempting to support their arguments of incorporating literature into language teaching a considerable number of researchers offer a number of reasons why literature is an ideal medium for extending language use. By means of inclusion of literature in language teaching, learners are at an advantage to acquire profound knowledge of language. The present paper investigates the language-literature division and focuses on the three phases with regard to the inclusion of literature in language teaching. The supportive role of literature in the development of language awareness is another issue the paper deals with.